Numerical simulation of inclined filament under biomagnetic fluid flow - Dinesh Kumar Ravada; Ranjith Maniyeri (Computer Assisted Methods in Engineering and Science, 2025)
The present study investigates the impact of magnetic field on the interaction of stationary, rigid filament-like structures in biomagnetic fluid flow, which has broad applications in mixing, transport, targeted drug delivery, and the development of magnetic devices. This work focuses on modeling a stationary, rigid, inclined filament fixed at the bottom of a channel within biomagnetic flow using the immersed boundary method. The inclined filament is positioned at various angles (θ = 450, 900 and 1350) in biomagnetic flow. Numerical simulations reveal that the fluid-filament interaction exhibits increased recirculation zones downstream when influenced by a magnetic field. Interestingly, when the filament is placed at θ = 450, there is a reduction in vortex formation upstream. The study also examines the effect of parameters such as the Reynolds number (Re) and the magnetic number (Mn) on the size of vortex formation. It is evident that as the Re and Mn increase the size of recirculation zones and secondary vortex formation also increases.